Recruiting, Hiring, and Training Alaska's Rural Teachers: How Superintendents Practice Place-Conscious Leadership - Dayna Jean DeFeo; Trang C. Tran (Journal of Research in Rural Education, 2019)
This article describes how superintendents approach the administrative processes of recruiting, hiring, and training new teachers to work in Alaska's rural schools. Drawing from interviews of superintendents and administrators in 32 rural Alaska school districts, the data show not only the amount of time and responsibility that rural superintendents commit to these activities, but also how they regard community as central in guiding their execution of these tasks. Our findings underscore the integral role of rural superintendents in setting a place-conscious leadership tone for the districts they serve, as well as the risk of losing institutional memory and networks when these positions turn over.